Enhancing physical characteristics and antibacterial efficacy of chitosan through investigation of microwave-assisted chemically formulated chitosan-coated ZnO and chitosan/ZnO physical composite - Sara A. Ali; E. S. Ali; G. Hamdy; Mona Shaban E. M. Badawy; Abdallah R. Ismail; Inas. A. El-Sabbagh; Magda M. El-Fass; Moataz A. Elsawy (Scientific Reports, 2024)
Abstract This study investigates the creation and analysis of chitosan-zinc oxide (CS-ZnO) nanocomposites, exploring their effectiveness in inhibiting bacteria. Two synthesis approaches, physical and chemical, were utilized. The CS-ZnO nanocomposites demonstrated strong antibacterial properties, especially against Staphylococcus aureus, a Gram-positive bacterium. Chemically synthesized nanocomposites (CZ10 and CZ100) exhibited larger inhibition zones (16.4 mm and 18.7 mm) compared to physically prepared CS-Z5 and CS-Z20 (12.2 mm and 13.8 mm) against Staphylococcus aureus. Moreover, CZ nanocomposites displayed enhanced thermal stability, with decomposition temperatures of 281°C and 290°C, surpassing CS-Z5 and CS-Z20 (260°C and 258°C). The residual mass percentages at 800°C were significantly higher for CZ10 and CZ100 (58% and 61%) than for CS-Z5 and CS-Z20 (36% and 34%). UV–Visible spectroscopy revealed reduced band gaps in the CS-ZnO nanocomposites, indicating improved light absorption. Transmission electron microscopy (TEM) confirmed uniform dispersion of ZnO nanoparticles within the chitosan matrix. In conclusion, this research underscores the impressive antimicrobial potential of CS-ZnO nanocomposites, especially against Gram-positive bacteria, and highlights their enhanced thermal stability. These findings hold promise for diverse applications in industries such as medicine, pharmaceuticals, and materials science, contributing to the development of sustainable materials with robust antimicrobial properties.